2020
DOI: 10.1007/jhep05(2020)134
|View full text |Cite
|
Sign up to set email alerts
|

Holographic interfaces in $$ \mathcal{N} $$ = 4 SYM: Janus and J-folds

Abstract: We find the holographic dual to the three classes of superconformal Janus interfaces in N = 4 SYM that preserve three-dimensional N = 4, N = 2, and N = 1 supersymmetry. The solutions are constructed in five-dimensional SO(6) maximal gauged supergravity and are then uplifted to type IIB supergravity. Corresponding to each of the three classes of Janus solutions, there are also AdS 4 × S 1 × S 5 J-fold backgrounds. These J-folds have a non-trivial SL(2, Z) monodromy for the axio-dilaton on the S 1 and are dual t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(147 citation statements)
references
References 51 publications
9
138
0
Order By: Relevance
“…A sample solution is plotted in figure 2. This solution can be uplifted to a ten-dimensional solution of type IIB supergravity as explicitly demonstrated in [13]. There it was also shown that the uplifted solution reproduces the ten-dimensional Janus backgrounds found previously in [12].…”
Section: N = 4 Janussupporting
confidence: 68%
See 2 more Smart Citations
“…A sample solution is plotted in figure 2. This solution can be uplifted to a ten-dimensional solution of type IIB supergravity as explicitly demonstrated in [13]. There it was also shown that the uplifted solution reproduces the ten-dimensional Janus backgrounds found previously in [12].…”
Section: N = 4 Janussupporting
confidence: 68%
“…A type IIB dual of the N = 4 interface was constructed directly in ten dimensions in [12]. Here I review the five-dimensional construction of the holographic duals to the N = 2 and N = 4 interfaces in N = 4 SYM which were first constructed in [13]. These can also be uplifted to ten dimensions using the formulae in [14].…”
Section: Pos(corfu2019)132mentioning
confidence: 99%
See 1 more Smart Citation
“…The supersymmetric Janus supergravity solutions corresponding to[26] have recently been discussed in[31]. From[31] one can check that the there are no source terms for the dimension ∆ = 2, 3 operators away from the interface, consistent with[26].…”
mentioning
confidence: 99%
“…From a contemporary perspective, curved BPS domain walls appear mainly in two different contexts of supergravity. One is as Janus solutions which have AdS space as the slice [9][10][11][12][13][14][15][16][17][18][19][20][21], and the other is holographic renormalization group flow with mass deformation dual to gauge field theory defined on the sphere [22][23][24][25][26], which is of our interest in this paper. Note that, applying the Hamilton-Jacobi formalism to general relativity problems, in particular to holographic renormalization and AdS black holes where the radial coordinate is interpreted as "time" has a long history [27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Jhep10(2020)068mentioning
confidence: 99%